PPAR-<svg style="vertical-align:-0.216pt;width:11.7125px;" id="M1" height="16.35" version="1.1" viewBox="0 0 11.7125 16.35" width="11.7125" xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg"> <g transform="matrix(.022,-0,0,-.022,.062,16.025)"><path id="x1D6FF" d="M494 514l-10 -15q-56 76 -106.5 117t-110.5 41q-45 0 -45 -30q0 -28 109 -152q59 -68 86 -118.5t27 -107.5q0 -62 -29.5 -119.5t-86.5 -96.5q-64 -45 -138 -45q-76 0 -121.5 53t-45.5 136q0 74 40.5 135t98.5 95q43 26 87 42q-40 59 -57.5 92t-17.5 62q0 46 39 77.5 t90 31.5q54 0 97.5 -35.5t65 -78.5t28.5 -84zM359 234q0 84 -90 191q-47 -17 -74 -47q-81 -89 -81 -200q0 -71 32.5 -109.5t72.5 -38.5q47 0 80 33t46.5 77.5t13.5 93.5z" /></g> in Vascular Pathophysiology - Wang, Nanping (PPAR Research, 2008)
Peroxisome proliferator-activated receptors belong to the superfamily of ligand-dependent nuclear receptor transcription factors, which include three subtypes: PPAR-α, β/δ, and γ. PPAR-δ, play important roles in the regulation of cell growth and differentiation as well as tissue wound and repair. Emerging evidence has also demonstrated that PPAR-δ is implicated in lipids and glucose metabolism. Most recently, the direct effects of PPAR-δ on cardiovascular processes such as endothelial function and angiogenesis have also been investigated. Therefore, it is suggested that PPAR-δ may have critical roles in cardiovascular pathophysiology and is a potential target for therapeutic intervention of cardiovascular disorders such as atherosclerosis.